Efficacy of 1 g Ceftriaxone Monotherapy Compared to Dual Therapy With Azithromycin or Doxycycline for Treating Extragenital Gonorrhea Among Men Who Have Sex With Men - Aoki, Takahiro; Mizushima, Daisuke; Takano, Misao; Ando, Naokatsu; Uemura, Haruka; Yanagawa, Yasuaki; Watanabe, Koji; Gatanaga, Hiroyuki; Kikuchi, Yoshimi; Oka, Shinichi (Clinical infectious diseases, 2021)
Evidence on efficacy of high-dose ceftriaxone monotherapy for extragenital Neisseria gonorrhoeae (NG) infection is lacking.BACKGROUNDEvidence on efficacy of high-dose ceftriaxone monotherapy for extragenital Neisseria gonorrhoeae (NG) infection is lacking.A cohort of men who have sex with men (MSM) were tested for NG/Chlamydia trachomatis (CT) every 3 months, in a single-center observational study in Tokyo, Japan. MSM aged > 19 years diagnosed with extragenital NG infection between 2017 and 2020 were included. A single dose of 1 g ceftriaxone monotherapy was provided, while dual therapy with a single oral dose of 1 g azithromycin or 100 mg doxycycline administered orally twice daily for 7 days were given, for those coinfected with CT, according to infected sites. Efficacy of these treatments was calculated by the number of NG-negative subjects at test-of-cure divided by the number of subjects treated. Fisher exact tests were used to compare the efficacy between the 2 groups.METHODSA cohort of men who have sex with men (MSM) were tested for NG/Chlamydia trachomatis (CT) every 3 months, in a single-center observational study in Tokyo, Japan. MSM aged > 19 years diagnosed with extragenital NG infection between 2017 and 2020 were included. A single dose of 1 g ceftriaxone monotherapy was provided, while dual therapy with a single oral dose of 1 g azithromycin or 100 mg doxycycline administered orally twice daily for 7 days were given, for those coinfected with CT, according to infected sites. Efficacy of these treatments was calculated by the number of NG-negative subjects at test-of-cure divided by the number of subjects treated. Fisher exact tests were used to compare the efficacy between the 2 groups.Of 320 cases diagnosed with extragenital NG, 208 were treated with monotherapy and 112 were treated with dual therapy. The efficacy against total, pharyngeal, and rectal infections was 98.1% (204/208, 95% confidence interval [CI]: 95.2-99.3%), 97.8% (135/138, 95% CI: 93.8-99.4%), and 98.6% (69/70, 95% CI: 92.3-99.9%), respectively, in the monotherapy group, whereas the corresponding efficacy in the dual therapy was 95.5% (107/112, 95% CI: 90.0-98.1%), 96.1% (49/51, 95% CI: 86.8-99.3%), and 95.1% (58/61, 95% CI: 86.5-98.7%), respectively. No significant difference in the corresponding efficacy was observed between the two groups (P = .29, P = .61, P = .34, respectively).RESULTSOf 320 cases diagnosed with extragenital NG, 208 were treated with monotherapy and 112 were treated with dual therapy. The efficacy against total, pharyngeal, and rectal infections was 98.1% (204/208, 95% confidence interval [CI]: 95.2-99.3%), 97.8% (135/138, 95% CI: 93.8-99.4%), and 98.6% (69/70, 95% CI: 92.3-99.9%), respectively, in the monotherapy group, whereas the corresponding efficacy in the dual therapy was 95.5% (107/112, 95% CI: 90.0-98.1%), 96.1% (49/51, 95% CI: 86.8-99.3%), and 95.1% (58/61, 95% CI: 86.5-98.7%), respectively. No significant difference in the corresponding efficacy was observed between the two groups (P = .29, P = .61, P = .34, respectively).High-dose ceftriaxone monotherapy is as effective as dual therapy for extragenital NG among MSM.CONCLUSIONSHigh-dose ceftriaxone monotherapy is as effective as dual therapy for extragenital NG among MSM.